Seasonal variations of protein in the ovary of fish Channa gachua - S.E. Shinde, R .Y. Bhandare, D.L. Sonawane, V.F. Dabhade, T.S. Pathan (Recent Research in Science and Technology, 2009)
The present study was carried out in the breeding seasons from 2004 to 2006. The ovary of fresh water fish Channa gachua was analyzed for its protein content during period of four different phases of reproductive cycle, in Channa gachua i.e. preparatory, pre-spawning, and post-spawning. Protein content found in preparatory phase was non significant, and significantly increased from pre-spawning to spawning and declined in post-spawning (mg/g wet weight of ovary).